Microbial Community Analysis Offers Insight into the Complex Origins of Plant Disease in a Smallholder Farm Context - Betsy A. Alford; Dagnachew Bekele; Sultan M. Yimer; Amna Fayyaz; Noelia Carrasquilla-Garcia; Peter L. Chang; Calen Badger; Anandkumar Surendrarao; Eric J. B. von Wettberg; M. Farooq H. Munis; Kassahun Tesfaye; Asnake Fikre; et al. (Phytobiomes Journal, 2024)
Classical approaches to plant disease diagnosis assume a single pathogen/single disease paradigm. Here, we revisit the presumed role of Fusarium oxysporum as the causal agent of wilting and yellowing of chickpea plants on smallholder farms in Ethiopia. Contrary to expectations, detection of Fusarium DNA using conserved PCR primers failed to associate the pathogen with symptomatic plants. Instead, culture-independent sequencing of microbial communities nominated unexpected pathogens and revealed patchiness in the assembly of common microbial consortia. Surprisingly, tests of differential enrichment identified Phytophthora as the most common disease-associated taxon. More generally, across all field sites, multilevel pattern analysis identified indicator taxa whose patterns of co-occurrence demarcate discrete microbial communities and are consistent with a range of specific interactions, including mutualism and antagonism. Taken together, these data indicate that soilborne chickpea disease in Ethiopia has heterogeneous origins and that despite decades of emphasis and disease resistance breeding, the role of Fusarium as the frequent agent of chickpea disease in Ethiopia remains enigmatic.